'A well-dressed actress': Exploring the Theatrical Wardrobe of Ellen Terry. (March 2018) - Isaac, Veronica
Abstract : A leading actress of the late nineteenth century, Dame Ellen Terry (1847–1928) exercised an unusual degree of control over her theatre costumes and played an active role in the design and creation of these garments. Drawing upon evidence gathered from a wide range of material culture sources, most notably her surviving costumes, this article considers the theatrical, historical, social and artistic context which shaped Terry's theatrical performances and stage dress. Terry's theatre costumes also reflected her personal views on dress, both on and off the stage. Particular attention will therefore be paid to the changes which occurred in Terry's stage dress as her increasing fame and financial independence enabled her to achieve greater control over the design and, importantly, the designers, of her theatre costumes. Through a close analysis of key pieces from Terry's stage wardrobe, this article will draw attention to the important part her theatre costumes played in a wider process of self-fashioning in which Terry used her dress, both on and off the stage, to establish her status as an 'Icon of Aestheticism' and secure her enduring legacy as an actress who understood the 'art' of theatre.